Simplified Accounting System for Small Business Entities - Mominjonov , Alisher (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the simplified accounting system for small business entities from both theoretical and practical perspectives. The study examines the regulatory and legal framework of the Republic of Uzbekistan in the field of accounting and taxation, assessments conducted by international organizations, and recent statistical sources to compare various simplification concepts. The first section of the article outlines the purpose, principles, and legal foundations of simplified reporting, including relevant regulations such as the Law “On Accounting” and practical implementation tools. The second section analyzes the advantages and limitations of the simplified system in terms of accurately and promptly reflecting the financial performance of small enterprises, improving tax efficiency, and reducing administrative burden. The third section presents practical examples, departmental statistics, and international recommendations, offering policy proposals such as the standardization of financial reporting, the introduction of electronic reporting systems, and the development of training programs for accountants and entrepreneurs. The main conclusion of the study is that a simplified accounting system contributes to increasing economic efficiency by promoting the formalization and digitalization of small businesses. However, its effectiveness largely depends on clear regulation and practical support mechanisms.